BASE SURFACE TEMPERATURE OF BULK FILL RESIN COMPOSITE WITH DIFFERENT THICKNESS - Harahap, Sefty Aryani; Yudhit, Astrid; Febyola, Vivi Niwani; Harahap, Naspati; Candra, Graciella (FKG ULM, 2024)
Background: The material thickness is one factor that influences the polymerization of resin composites. Bulk fill resin composite is an efficient dental resin composite restoration material because it can be cured to a thickness of up to 4-5 mm. The thickness of the material can also affect the temperature rise, while maintaining the temperature is very important because a significant increase can damage the pulp. Purpose: This research aimed to analyze the base surface temperature of bulk fill resin composite with different thicknesses. Methods: Thirty bulk fill resin composite samples with a diameter of 5 mm were divided into three groups with different thicknesses, namely group I (3 mm), group II (4 mm), and group III (5 mm). Each group of samples was cured using an LED Light Curing Unit for 20 seconds, and carried out simultaneously with the measurement of the base surface temperature using a type-K digital thermocouple. Data analyzed using One Way ANOVA and LSD post hoc tests. Results: The mean and standard deviation of the base surface temperature of bulk fill resin composite in groups I, II, and III, respectively, is 37.56 ± 1.06oC, group II 36.89 ± 1.23oC, and group III 36.00 ± 1.2 oC. It showed significantly different between the groups (p<0,05). Conclusion: The thicker the bulk fill resin composite, the lower the base surface temperature.